FISHING SEASON REVIEW BILIS / TERI (Stelopherus Spp) IN THE DISTRICT OF ASAM WATERS STRAIT MERANTI ISLANDS PROVINCE RIAU - Akbar Karim Nasution; T. Ersty Y ulika Sari; Usman ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
Has conducted a study to determine the pattern of fishing season bilis (Stolephorus Spp.) in the waters of the Strait Asam Meranti Islands regency of Riau Province with method survey /direct observation, with use some formulas including average, variance, standard deviation, maximum value, minimum value and range. Based on the analysis, patterns bilis season in waters of the strait starts from the beginning of December to March and July to September and entered the peak months in January and August, the first transitional season in April-June and October-November switchover II. the catch is affected by the monsoon, season affected the West Wind and East Wind ongoing season, when the North and South Season (transitional season) bilis difficult to obtain due to the influence of big waves and temperature begin to warm water.Key words: pattern wind season, the average catch, the fishing season bilis